INFLUENCE OF WORK-LIFE CONFLICT ON AGRICULTURAL EMPLOYEE’S JOB PERFORMANCE IN FOREST RESEARCH INSTITUTE OF NIGERIA (FRIN), OYO STATE, NIGERIA - Abiona, B G; Adeogun, S O; Alade, M S (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
Work is an integral part of human life with or without human existence will be difficult. This study determined the influence of work-life conflict on agricultural employee’s job performance at Forestry Research Institute of Nigeria in Ibadan Oyo State, Nigeria. The objectives were: description of employee’s personal characteristics, determination of work-life conflict and level of employee’s job performance and identification of challenges faced by the respondents in the study area. Multistage Sampling technique was used to select 76 respondents through a well-structured questionnaire. Data collected were analyzed through both descriptive and inferential statistical tools. The results shows the mean age to be 33 years, 51.3% were male, 73.7% were married, and majority 92.1% were Christian and mean income was ₦41.592 per month.  Furthermore, major work life conflict identified by the respondents were: work as primary priority (  = 4.2), training overseas (  = 4.32), information technology (  = 4.32). More so, quality of information technology (  =4.32), oversea training (  =4.26) and having interest in their current job (  =4.18) were indicators that enhance employees job performance. Major challenges faced by the organization were present economy affects their job performance (  = 3.23), poor working condition (  = 2.80) and lack of research materials (  = 2.56). The results also show that level of work-life conflict with coefficient value of (0.036), age (0.041), income (0.029) and challenges (0.04) were variable influencing employee’s job performance. In conclusion that work-life conflicts have a negative effect on family life in term of number of hours spent at work. Provision of healthy balance system between employee’s professional role and family responsibilities is highly recommended.